The impact of information security events to the stock market: A systematic literature review. Issue 58 (May 2016) - Spanos, Georgios; Angelis, Lefteris
Abstract: Information security is a highly critical aspect of information systems. Although the literature regarding security assurance is vast, the research on economic consequences of security incidents is quite limited. The purpose of this systematic review is to search, collect and classify event studies related to information security impact on stock prices. In total, 37 related papers conducting 45 studies were found by the systematic search of bibliographic sources. The majority (75.6%) of these studies report statistical significance of the impact of security events to the stock prices of firms.